Literatura, ciência e a formação do leitor na educação básica - Marques, Kellyne Amaral (2023)
Our research project will work with an interdisciplinary proposal, which will have as its main the reading of the adaptation of Jules Verne by Cony, Viagem ao centro da terra, with students of the 9th year of elementary school of a public school. The reading of the literary texts will be mediated by the research professor, through a process of interaction, in which the student will have opportunities to dialogue about their understandings, their point of view and expectations about the texts addressed in the classes, aiming at the aesthetic reception of the texts read. At the end, he will have the opportunity to act on the main text read in rewrite form. The research will be based on the theoretical contributions of literary literacy, subjective reading and creative writing. In this perspective, the research professor will have the fundamental role of mediating the entire process under construction. Our intention is to foster in students the interest in literary reading and the area of Nature Sciences. To this end, we will offer, in addition to the mediation of reading a work of science fiction, a discussion about the relevance of research and scientific knowledge to society. Therefore, in addition to providing the reading of the literary text, we will also offer dialogues with the main work through readings and discussions of the theme of reports, virtual visits in important museums and also presentation of the film based on the work of Jules Verne. The pedagogical intervention planned for this research is based on Thiollent's action research methodology (2000).